2022
DOI: 10.3389/fonc.2022.858782
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation-Dependent Regulation of WNT/Beta-Catenin Signaling

Abstract: WNT/β-catenin signaling is a highly complex pathway that plays diverse roles in various cellular processes. While WNT ligands usually signal through their dedicated Frizzled receptors, the decision to signal in a β-catenin-dependent or -independent manner rests upon the type of co-receptors used. Canonical WNT signaling is β-catenin-dependent, whereas non-canonical WNT signaling is β-catenin-independent according to the classical definition. This still holds true, albeit with some added complexity, as both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 188 publications
(243 reference statements)
1
26
0
Order By: Relevance
“…55 PKCδ phosphorylates βcatenin at Ser715 and targets it for β-Trcp-independent ubiquitination and degradation. 56,57 Protein kinase A (Ser-552 and Ser-675), c-Jun N-terminal kinase 2 ([JNK-2], Ser191 and Ser605), p21-activated kinase (Ser675), and Akt (Ser552) phosphorylate βcatenin and enhance its transcriptional activity. [58][59][60][61] Moreover, Src (Tyr86, Tyr142, and Tyr654) and receptor tyrosine kinases (Tyr142) phosphorylate βcatenin at multiple sites and stimulate its dissociation from cadherins and αcatenin and release from adhesion complexes.…”
Section: Wnt Ligands and Receptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…55 PKCδ phosphorylates βcatenin at Ser715 and targets it for β-Trcp-independent ubiquitination and degradation. 56,57 Protein kinase A (Ser-552 and Ser-675), c-Jun N-terminal kinase 2 ([JNK-2], Ser191 and Ser605), p21-activated kinase (Ser675), and Akt (Ser552) phosphorylate βcatenin and enhance its transcriptional activity. [58][59][60][61] Moreover, Src (Tyr86, Tyr142, and Tyr654) and receptor tyrosine kinases (Tyr142) phosphorylate βcatenin at multiple sites and stimulate its dissociation from cadherins and αcatenin and release from adhesion complexes.…”
Section: Wnt Ligands and Receptorsmentioning
confidence: 99%
“…62,63 Src and receptor tyrosine kinases also promote its interaction with nuclear partners, but protein kinase D1 phosphorylates (Thr112 and Thr120) and stimulates βcatenin interactions with αcatenin and cadherins. 56,[64][65][66] F I G U R E 1 WNT/β-catenin signaling pathway in cardiomyocytes. (A) In unstimulated cells, WNT/β-catenin signaling is inactive, and the cytoplasmic βcatenin pool is sequestered in the destruction complex that undergoes permanent phosphorylation and degradation.…”
Section: Wnt Ligands and Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…To illustrate, cisplatin-resistant non-small cell lung cancer (NSCLC) cell line showed upregulation of β-catenin due to phosphorylation-dependent inhibition of GSK3β [42] , and cisplatin-resistant hepatocellular carcinoma cells exhibited nuclear accumulation of GSK3β [43] . GSK3β is an essential component of the destruction complex that maintains a β-catenin cellular level by inducing phosphorylation-dependent degradation [44] . Stabilization of β-catenin, caused by phosphorylation-dependent inhibition of GSK3β, facilitates nuclear translocation and transcription of WNT response genes.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that the FBXW7-185aa protein encoded by circ-FBXW7 could inhibit ubiquitination of the parent gene protein by competitively binding USP28, thus downregulating c-MYC expression and inhibiting the occurrence and development of breast cancer. The abnormal activation of Wnt/β-catenin signaling pathways was closely associated with increased prevalence, malignant progression, development of poor prognosis, and even increased cancer-related mortality ( 45 ). Liang et al.…”
Section: The Role and Molecular Mechanisms Of Circrnas Regulating Par...mentioning
confidence: 99%